Single-molecule visualization of a formin-capping protein ‘decision complex' at the actin filament barbed end - Bombardier, Jeffrey P. (Nat Commun, 2015)
Precise control of actin filament length is essential to many cellular processes. Formins processively elongate filaments, whereas capping protein (CP) binds to barbed ends and arrests polymerization. While genetic and biochemical evidence has indicated that these two proteins function antagonistically, the mechanism underlying the antagonism has remained unresolved. Here we use multi-wavelength single-molecule fluorescence microscopy to observe the fully reversible formation of a long-lived ‘decision complex' in which a CP dimer and a dimer of the formin mDia1 simultaneously bind the barbed end. Further, mDia1 displaced from the barbed end by CP can randomly slide along the filament and later return to the barbed end to re-form the complex. Quantitative kinetic analysis reveals that the CP-mDia1 antagonism that we observe in vitro occurs through the decision complex. Our observations suggest new molecular mechanisms for the control of actin filament length and for the capture of filament barbed ends in cells.